Can Muslims Fly? The No Fly List as a Tool of the "War on Terror". Issue 1 (1st October 2017) - Uzma Jamil
Abstract : The securitization phenomenon is based on a racialized logic that predates 9/11 and has roots in the discourse of Orientalism, the practices of European colonialism and, in the more recent times of the 20th century, the internment of Japanese Canadians during World War II. This article analyzes the "no fly list" as a counter-terrorism tool used by the Canadian government in the "war on terror." It situates the analysis in the political context of the securitization of Muslims, the social and political processes that construct them as threats to the nation. It examines the evolution of the "no fly list" since 2001 and analyzes its impact on Muslims in Canada, drawing on well-publicized cases. It critiques the list's effectiveness based on the distinction between information and knowledge as tools to fight the "war on terror." The "no fly list" contributes to Islamophobia through disproportionately profiling racialized Muslim and Muslim-looking passengers as members of a suspect community.